2008
DOI: 10.1002/dneu.20660
|View full text |Cite
|
Sign up to set email alerts
|

Experience‐dependent refinement of the inhibitory axons projecting to the medial superior olive

Abstract: Neurons in the medial superior olive (MSO) analyze interaural time differences (ITDs) by comparing the arrival times of the two excitatory inputs from each ear using a coincidence detection mechanism. They also receive a prominent inhibitory, glycinergic projection from the ipsilateral medial nucleus of the trapezoid body (MNTB), which contributes to the fine-tuning of ITD analysis. Here, we investigated developmental changes of the axonal arborisation pattern of single Microruby-labeled MNTB neurons projectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 26 publications
5
61
1
Order By: Relevance
“…This finding is surprising in light of previous anatomical findings suggesting a synaptic refinement of inhibitory inputs (Kapfer et al 2002;Werthat et al 2008). This invariance may indicate that the mature functional GlyR gradient (biased toward the soma and proximal dendrites) is already established in the MSO at this age.…”
Section: Resultscontrasting
confidence: 76%
See 2 more Smart Citations
“…This finding is surprising in light of previous anatomical findings suggesting a synaptic refinement of inhibitory inputs (Kapfer et al 2002;Werthat et al 2008). This invariance may indicate that the mature functional GlyR gradient (biased toward the soma and proximal dendrites) is already established in the MSO at this age.…”
Section: Resultscontrasting
confidence: 76%
“…Anatomically, the developmentally driven restriction of inhibitory inputs to the soma and proximal dendrites of MSO neurons is well documented (Couchman et al 2010;Kapfer et al 2002;Kuwabara and Zook 1992;Werthat et al 2008). To date, though, there has been no functional investigation to confirm this morphological arrangement.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Together with the ultrastructural evidence for multiple release sites per synapse (Clark, 1969;Lindsey, 1975;Kiss and Majorossy, 1983;Brunso-Bechtold et al, 1990;Kapfer et al, 2002), this anatomically derived number matches well our physiological estimates of the number of presynaptic inhibitory release sites. Furthermore, we confirmed that one MNTB fiber innervates between 1 and 7 MSO neurons (Werthat et al, 2008).…”
Section: Size and Strength Of Excitatory Fibers To Mso Neuronssupporting
confidence: 72%
“…Image stacks were processed with ImageJ, MetaMorph (Universal Imaging Corp., Visitron Systems GmbH), and Neurolucida (MBF Bioscience) to extract varicosity number and synaptic number by eye. For Figure 7 (see below), the acquired images were further processed in NIH ImageJ 1.37k (National Institutes of Health) as described by Werthat et al (2008). Individual cell processes visible on each optical section of MAP-2 staining were followed through the stack and labeled with the paintbrush tool.…”
Section: Methodsmentioning
confidence: 99%